2016
DOI: 10.1021/acs.est.6b03555
|View full text |Cite
|
Sign up to set email alerts
|

Bacteria Inactivation during the Drying of Struvite Fertilizers Produced from Stored Urine

Abstract: Human urine can be processed into market-attractive fertilizers like struvite; however, concerns regarding the microbial safety of such products remain. The present study evaluated the inactivation of in situ heterotrophs, total bacteria as observed by flow cytometry, and inoculated Enterococcus spp. and Salmonella typhimurium during the drying of struvite under controlled temperature (from 5 to 35°C) and relative humidity (approximately 40 and 80%) as well as dynamic field conditions. Bacteria accumulated in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Though the dry sample was not tested, postprecipitation processing steps will be integral for microbial reduction should spore-formers be considered an important class of AMR hazard. It has been previously shown that an accumulation of bacteria can occur during the filtration process of struvite production . The results of the study indicated that heating under moist conditions followed by desiccation would increase the inactivation efficiency .…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Though the dry sample was not tested, postprecipitation processing steps will be integral for microbial reduction should spore-formers be considered an important class of AMR hazard. It has been previously shown that an accumulation of bacteria can occur during the filtration process of struvite production . The results of the study indicated that heating under moist conditions followed by desiccation would increase the inactivation efficiency .…”
Section: Resultsmentioning
confidence: 87%
“…The results of the study indicated that heating under moist conditions followed by desiccation would increase the inactivation efficiency . The drying temperature and moisture content were shown to play a role in the bacterial inactivation in which a low relative humidity allowed bacteria to persist, further indicating the importance of postprecipitation treatment steps …”
Section: Resultsmentioning
confidence: 94%
“… Decrey et al. (2011) and Bischel et al. (2016) investigated the inactivation of virus phages, helminth eggs ( Ascaris suum ), heterotrophic and total bacteria, as well as Enterococcus spp.…”
Section: Removal Of Pathogens and Organic Micropollutantsmentioning
confidence: 99%
“…Meanwhile, municipal wastewater contains a large amount of phosphorus, which can cause eutrophication when released into water bodies in excess. To reconcile the simultaneous shortage and overabundance of phosphorus, struvite crystallization technique was developed. ,, Struvite, known as magnesium ammonium phosphate hexahydrate (MgNH 4 PO 4 ·6H 2 O), crystallizes in the orthorhombic system. , Due to its high phosphorus and nitrogen content and low solubility, struvite has been considered as an ideal slow-release fertilizer. ,,, In a specific reactor, struvite precipitation could be achieved by additional supplementation of Mg 2+ and NaOH into wasterwater, where Mg 2+ and pH all tend to be deficient for struvite precipitation. ,, In this way, phosphorus and nitrogen can be removed and recovered from wastewaters as reusable struvite. , In this regard, struvite crystallization technique can not only provide a means of phosphorus recovery, but also mitigate eutrophication of water bodies. Moreover, it is also reported that the deliberate struvite crystallization can help to solve scaling problems in wastewater treatment plants (WWTPs), and reduce sludge volumes. , Therefore, struvite precipitation has been regarded as a promising route to phosphorus recovery from wastewaters, and received increasing attention in recent years. ,, …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is also reported that the deliberate struvite crystallization can help to solve scaling problems in wastewater treatment plants (WWTPs), and reduce sludge volumes. 9,18 Therefore, struvite precipitation has been regarded as a promising route to phosphorus recovery from wastewaters, and received increasing attention in recent years. 3,10,19−24 However, the successful implementation of struvite precipitation in WWTPs depends on its economical sustainability.…”
Section: ■ Introductionmentioning
confidence: 99%